Oliver twist - Dickens, Charles (Penguin active reading, 2008)
This book is about Oliver's mother dying when he was born and him being raised in a workhouse. His first years are cold and lonely - and then he runs away to London. But he falls into the hands of Fagin and the terrifying Bill Sykes. They try to turn Oliver into a criminal. Will he escape to find a better life?